Feuerbach's Immortality (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This research deals with the concept of immortality as it emerges in modern philosophy, especially with the pioneers, such as Spinoza, Fichte, and Schelling. Also, this research deals with immortality before Feuerbach and tries to put it in its materialistic and idealistic framework, especially at the beginnings of Spinoza's materialistic thought who has suspicion about the materialism and eternity of the world. Thus, we call it desperate immortality in contrast to another kind of immortality that resorted to the idealistic framework, as German Idealism has expressed. The best who represent it are Fichte and Schelling who try to present a kind of deceitful immortality. In fact, this kind of immortality aims to separate Man from the real world, and this concept we have talked about in the concept of Man of immortality and how Feuerbach managed to put Man on his right path. This comes after Feuerbach's discovery and confirmation of what we have called the presence of immortality.